Dyes Removal from Wastewater by Coral Reef Waste as a Low-Cost Adsorbent - Umi Baroroh; Adang Firmansyah; Deni Deni; Lina Maudyawati; Ahmad Zainuddin (Syarif Hidayatullah State Islamic University, 2022)
Despite the positive impact of the rapid industrial growth in Indonesia, it has caused several problems. The non-biodegradable pollutant, such as reactive dyes that result from the textile industry, is harmful to the environment and human health. This contaminating agent should be removed from the waste before being disposed to the surrounding ecosystem. Adsorption is one of the simple and low-cost techniques to eliminate dye from the effluent. Waste from coral reefs is interesting to be explored as a dye-removing adsorbent because it is abundant in nature, cheap, and reusable. Therefore, this study aims to determine the adsorption performance of coral reef waste in removing several dyes, i.e., methylene blue (MB), remazol brilliant blue (RBB), disperse orange (DO), and vinyl sulfone (VS) from wastewater. The adsorption capacity was determined to evaluate the effectiveness of coral reef waste in removing the dyes at the isotherm model. Adsorption capacity and isotherm model were used to evaluate the effectiveness of this natural adsorbent. Based on the percentage removal and coefficient distribution value, the removal selectivity of RBB was the best, followed by DO, VS, and MB, respectively. In conclusion, coral reef waste is promising to be developed as a low-cost adsorbent for removing dyes from wastewater.